Paratransit: Introduction to the special section - King, David (Journal of Transport and Land Use, 2015)
Over the past few years, private taxi, jitneys, and other paratransit services have blossomed in cities around the world. Scholars have noticed. Two things stand out immediately. First, we don’t know very much about how taxi and paratransit services affect travel behavior and mode choices. Second, we know even less about who uses these systems. Because these services tend to serve niche populations, it is difficult to assess who an “average” rider is. What we do know about taxi services and paratransit is that they are important complements of—and occasional substitutes for—conventional fixed-route transit. This special section of the Journal of Transport and Land Use presents three articles in which the authors examine complementary travel modes to conventional public transit systems. Together these three papers provide evidence of how informal and nontraditional transit operates in conjunction with established transit services as well as competes with certain types of services.